Lycopene Inhibits Reactive Oxygen Species-Mediated NF-κB Signaling and Induces Apoptosis in Pancreatic Cancer Cells - Jeong, Yoonseon (Nutrients, 2019)
Generation of excess quantities of reactive oxygen species (ROS) caused by mitochondrial dysfunction facilitates rapid growth of pancreatic cancer cells. Elevated ROS levels in cancer cells cause an anti-apoptotic effect by activating survival signaling pathways, such as NF-κB and its target gene expression. Lycopene, a carotenoid found in tomatoes and a potent antioxidant, displays a protective effect against pancreatic cancer. The present study was designed to determine if lycopene induces apoptosis of pancreatic cancer PANC-1 cells by decreasing intracellular and mitochondrial ROS levels, and consequently suppressing NF-κB activation and expression of NF-κB target genes including cIAP1, cIAP2, and survivin. The results show that the lycopene decreased intracellular and mitochondrial ROS levels, mitochondrial function (determined by the mitochondrial membrane potential and oxygen consumption rate), NF-κB activity, and expression of NF-κB-dependent survival genes in PANC-1 cells. Lycopene reduced cell viability with increases in active caspase-3 and the Bax to Bcl-2 ratio in PANC-1 cells. These findings suggest that supplementation of lycopene could potentially reduce the incidence of pancreatic cancer.